2011
DOI: 10.1242/jcs.068759
|View full text |Cite
|
Sign up to set email alerts
|

TOX3 is a neuronal survival factor that induces transcription depending on the presence of CITED1 or phosphorylated CREB in the transcriptionally active complex

Abstract: SummaryTOX3 is a nuclear protein containing a high mobility group (HMG)-box domain, which regulates Ca 2+ -dependent transcription in neurons through interaction with the cAMP-response-element-binding protein (CREB). TOX3 appears to be associated with breast cancer susceptibility and was previously shown to be expressed downstream of a cytoprotective cascade together with CITED1, a transcriptional regulator that does not bind directly to DNA. In the present study we show that TOX3 is predominantly expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 25 publications
3
69
1
Order By: Relevance
“…The SNP appears to be strongly associated with breast cancer susceptibility (Huijts et al, 2007;Stacey et al, 2007). Several reports have demonstrated that genetic variants in TNRC9 are associated with risk of ERpositive breast cancer (Liang et al, 2010;Dittmer et al, 2011). In our study, both ER-and PR-positive patients were more susceptible to breast cancer than ER-or PR-negative patients (Table 1).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The SNP appears to be strongly associated with breast cancer susceptibility (Huijts et al, 2007;Stacey et al, 2007). Several reports have demonstrated that genetic variants in TNRC9 are associated with risk of ERpositive breast cancer (Liang et al, 2010;Dittmer et al, 2011). In our study, both ER-and PR-positive patients were more susceptible to breast cancer than ER-or PR-negative patients (Table 1).…”
Section: Discussionsupporting
confidence: 55%
“…SNP rs3803662 lies 8 kb upstream of TNRC9 and has been observed to be associated with an increased risk of breast cancer in both BRCA1 and BRCA2 mutation carriers (Antoniou et al, 2008). The rs3803662 polymorphism is either restricted to or more strongly associated with estrogen receptor (ER)-positive tumors than those ERnegative cancers (Stacey et al, 2007;Garcia-Closas et al, 2008;Dittmer et al, 2011). Several epidemiological studies have evaluated the association between TNRC9 polymorphisms and breast cancer risk, but the results remain inconclusive according to different ethnic groups (Zheng et al, 2009;Li et al, 2009;Ruiz-Narváez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is involved in the regulation of calcium-dependent transcription and interacts with cAMP response element-binding protein (Yuan et al, 2009). In addition, TNRC9 can interact with CITED1 to increase transcription (Yuan et al, 2009;Dittmer et al, 2011). CITED1 is a transcription coregulator that enhances the activity of transcription factors such as ERs (Yahata et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Easton et al (2007) provided strong evidence that rs3803662 C>T, which lies 8 kb upstream of TNRC9/LOC643714, confers even greater BC risk than mutations in both BRCA1 and BRCA2. The rs3803662 polymorphism is either restricted to or more strongly associated with estrogen receptor (ER)-positive BC than ERnegative cases (Stacey et al, 2007;Garcia-Closas et al, 2008;Dittmer et al, 2011). Several GWAS have evaluated the relationship between this variant and BC risk, but their results remain to be verified in different ethnic groups Zheng et al, 2009;Ruiz-Narváez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…12). It was also reported that exogenous delivery of TNRC9 induced a complex with CREB that protected neuronal cells from cell death through activation of BCL-2 (13).…”
Section: Introductionmentioning
confidence: 93%